Evaluasi Kinerja Operasional BRT Trans Jateng Koridor 1 dan 6: Pendekatan Faktor Muat (Load Factor) - Narendra, Alfa; Y. Irnizarifka, Ardhiatma; Anisa, Fitri; Z. Hasanah, Ghaida; I. Fatati, Herlingga; H. Falakh, Maulana; Puspitasari, Pipit; Zulianti, Rizka; R. Auzia, Rohadatu; Husniyah, Tamimatul; A. Khairunisa, Ufaira; P. Sari, Yesi (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2026)
The implementation of pilot Bus Rapid Transit (BRT) systems in metropolitan agglomerations, such as Trans Jateng, plays a pivotal role in providing affordable public transportation, enhancing regional connectivity, and fulfilling Minimum Service Standards (MSS). This study evaluates the operational performance of two specific Trans Jateng corridors: Corridor 1 (Semarang – Bawen) and Corridor 6 (Semarang – Grobogan). The primary focus of this research is the analysis of time-series load factor data to assess bus performance. Data were gathered through on-board surveys utilizing Global Positioning System (GPS) devices and structured survey instruments. The data collection was conducted over a period of two weekdays and one weekend day. The analytical results indicate that both corridors experience significant kelebihan penumpang during peak hours, with load factors exceeding 170% in Corridor 1 and 110% in Corridor 6. Furthermore, this study identifies distinct fluctuations in passenger demand patterns between weekdays and weekends, as well as variations between individual trips within the same corridor. The findings reveal a notable disparity in average load factors. In Corridor 1 during weekdays, the load factor for the Semarang – Bawen route was 55.73%, while the Bawen – Semarang route reached 38.81%; on weekends, these figures shifted to 60.46% and 40.03%, respectively. In Corridor 6, the weekday load factor for the Semarang – Godong route was 46.05% and 39.25% for the reverse direction, whereas weekend figures were recorded at 51.49% and 34.68%. Given that the ideal minimum load factor is 70%, more systematic operational management is necessitated to maintain optimal service performance. Proposed recommendations include the dynamic adjustment of fleet size to align with demand levels—particularly during peak periods—and the implementation of more adaptive capacity management strategies. Such measures are intended to regulate load factors during high-demand intervals, enhance passenger comfort, and improve the overall operational efficiency of the transit service.